How NATO Adapts : Strategy and Organization in the Atlantic Alliance since 1950 - Johnston, Seth A. (Seth Allen), 1981- (Book collections on Project MUSE., 2017)
Students, scholars, and policy practitioners will find this a useful resource for understanding NATO, transatlantic relations, and security in Europe and North America, as well as theories about change in internationalinstitutions.